Disaster Management: Computer Networking Communication Medium – A Survey - Sukhvinder Singh Bamber (International Journal of Advanced Science and Technology, 2020)
Disaster Management is the combination of pre disaster warnings and the full use of the resources available at the time of disaster occurrence scalably, adapatably and reliably. Wireless Sensor Networks (WSNs) embedded in IoT finds widespread applications in disaster management. WSNs have the ability to sense the surroundings but still are not capable enough to capture all the events of disasters reliably. So to make the WSNs work in the odd circumstances, have to optimized in terms of network performance metrics like: modulation schemes, sensor motes and the topologies.